SARS-CoV-2: Immune Response Elicited by Infection and Development of Vaccines and Treatments - Canedo-Marroquín, Gisela; Saavedra, Farides; Andrade, Catalina A.; Berrios, Roslye V.; Rodríguez-Guilarte, Linmar; Opazo, María C.; Riedel, Claudia A.; Kalergis, Alexis M. (Frontiers in Immunology, 2020)
The World Health Organization (WHO) announced in March a pandemic caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). This new infectious disease was named Coronavirus Disease 19 (COVID-19), and at October 2020, more than 39,000,000 cases of SARS-CoV-2 detected worldwide leading to near 1,100,000 deaths. Clinically, COVID-19 is characterized by clinical manifestations, such as fever, dry cough, headache, and in more severe cases, respiratory distress. Moreover, neurological-, cardiac-, and renal-related symptoms have also been described. Clinical evidence suggests that migration of immune cells to the affected organs can produce an exacerbated release of proinflammatory mediators that contribute to disease and render the immune response as a major player during the development of the COVID-19 disease. Due to the current sanitary situation, the development of vaccines is imperative. Up to the date, 42 prototypes are being tested in humans in different clinical stages, with ten vaccine candidates undergoing evaluation in phase III clinical trials. In the same way, the search for an effective treatment to approach the most severe cases is also in constant advancement. Several potential therapies have been tested since COVID-19 was described, including antivirals, antiparasitic and immune modulators. Recently, clinical trials with hydroxychloroquine – a promising drug in the beginning- were suspended. In addition, the Food and Drug Administration (FDA) approved convalescent serum administration as a treatment for SARS-CoV-2 patients. Moreover, monoclonal antibody therapy is also under development to neutralize the virus and prevent infection. In this article, we describe the clinical manifestations and the immunological information available about COVID-19 disease. Furthermore, we discuss current therapies under study and the development of vaccines to prevent this disease.